The Relationship Between Knowledge Level and Visits to Elderly Posyandu in Payunga Village, Batudaa District - Hamna Vonny Lasanuddin; Rosmin Ilham; Rona Febriyona; Shinta Aswin Rahman (Universitas Ibn Khaldun Bogor, 2023)
The Elderly Integrated Service Post (Posyandu) is a forum for elderly health services, whether or not regular visits by the elderly to the posyandu can be influenced by the knowledge of the elderly. The purpose of this study was to determine the relationship between knowledge and visits to elderly posyandu in Payunga Village, Batudaa District. Analytical survey research design with a cross-sectional study approach, elderly population as many as 106 elderly, the number of samples of 52 people using accidental sampling techniques in this study. The results of the study were obtained by all respondents whose level of knowledge was lacking, visits to posyandu were categorized as irregular as many as 16 respondents (30.8%). Respondents whose level of knowledge is quite comparable between visits to posyandu are regular as many as 10 respondents (19.2%) and irregular as many as 10 respondents (19.2%). Respondents with a good level of knowledge were the majority of visits to posyandu categorized as regular as many as 12 respondents (23.1%) and irregular as many as 4 respondents (7.7%). The results of the chi-square statistical test obtained a p-value of 0.000 (α <0.05). Conclusion There is a relationship between the level of knowledge and visits to elderly posyandu in Payunga Village, Batudaa District. Thus, it is expected to provide health counseling for the elderly in Payunga Village regarding the importance of the elderly posyandu for the development of elderly health.